Inclusive development. How is Poland doing in comparison to other OECD countries? - Szymańska, Anita; Zielenkiewicz, Małgorzata (Wydawnictwo Uniwersytetu Rzeszowskiego, 2020)
Inclusive development is a multifaceted conception, which makes it difficult to measure. Recent years, however, have brought some proposals for measuring this phenomenon, which opens up new opportunities to deepen the knowledge of how countries are doing in making their economic and social progress more inclusive. The aim of the paper is to examine the level of advancement of inclusive development in Poland in comparison to other OECD countries. The main hypothesis states that the development in Poland is less inclusive than the OECD average. The research covers data from 30 countries (OECD members, excluding the countries where such data were unavailable), and is based on the OECD’s proposal of measurement. The study was conducted with the use of data normalisation into unified indices, taxonomic methods (cluster analysis based on the Ward hierarchic method), and comparative analysis. The results indicate areas of improvement for Poland. These are issues connected with the functioning of the labour market (the level of labour productivity, employment ratio, earnings dispersion), access to loans for starting or expanding businesses, but also life expectancy, wealth distribution, early childhood education and care, and, most of all, characteristics related to the area of governance, such as trust in the government, and voter turnout.

Rozwój inkluzywny jest pojęciem wielowymiarowym, co czyni go trudnym do zmierzenia. Jednak w ostatnich latach pojawiły się propozycje pomiaru tego zjawiska, które otwierają nowe możliwości pogłębienia wiedzy na temat tego, jak poszczególne kraje radzą sobie w czynieniu ekonomicznego postępu bardziej włączającym. Celem artykułu jest sprawdzenie poziomu zaawansowania inkluzywności rozwoju w Polsce w porównaniu do innych krajów OECD. Za główną hipotezę przyjęto w artykule stwierdzenie, że rozwój w Polsce jest mniej inkluzywny niż przeciętnie w OECD. Badanie obejmuje 30 krajów członkowskich OECD (pominięto te, dla których dane nie były dostępne) i opiera się na propozycji pomiaru rozwoju inkluzywnego opracowanej przez OECD. W badaniu wykorzystano normalizację danych do jednolitych indeksów, metody taksonomiczne (analiza skupień w wersji Warda) oraz analizę porównawczą. Wyniki badania pozwoliły wskazać obszary inkluzywności wymagające w Polsce poprawy. Są to kwestie związane z funkcjonowaniem rynku pracy (poziom wydajności pracy, stopa zatrudnienia, zróżnicowanie wynagrodzeń), dostęp do kredytów na rozpoczęcie lub rozszerzenie własnej działalności, ale także długość życia, dystrybucja majątku i wczesna opieka i edukacja oraz przede wszystkim czynniki związane z instytucjami publicznymi, takie jak zaufanie do rządu lub frekwencja wyborcza.
Keywords: inclusiveness; growth; development; economic and social exclusion; OECD; inkluzywność; wzrost; rozwój; wykluczenie ekonomiczne i społeczne